2003
DOI: 10.1152/japplphysiol.00441.2003
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic filling and systolic function of young and older trained and untrained men

Abstract: Left ventricular diastolic filling and systolic function of young and older trained and untrained men. J Appl Physiol 95: 2570-2575. First published July 25, 2003 10.1152/japplphysiol.00441.2003.-Aging is associated with impaired early diastolic filling; however, the effect of endurance training on resting diastolic function in older subjects is unclear. Heart rate and ventricular loading conditions affect mitral inflow velocities measured by Doppler echocardiography; therefore, tissue Doppler imaging of mitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 34 publications
(50 reference statements)
3
42
1
Order By: Relevance
“…In similar subjects, almost identical data (E/A athletes 1.9 ± 0.5 vs. control 1.6 ± 0.2) were either significant (Pluim et al 1998) or non-significant (Pluim et al 1999) based on sample size (21 vs. 12 male cyclists). Cross-sectional or flow propagation data from TDI studies tend to mirror the Doppler flow data described above, with limited differences in E 0 (Caso et al 2000;Schmidt-Trucksäss et al 2001;Pelà et al 2004;Baldi et al 2003), A 0 being similar or lower (Caso et al 2000;Schmidt-Trucksäss et al 2001;Pelà et al 2004;Tümüklü et al 2008;Kasikcioglu et al 2005;Zoncu et al 2002) and generally small improvement in the E 0 /A 0 ratio in athletes compared to untrained subjects. Nonetheless, studies of Olympic speed skaters (Poh et al 2008), professional soccer players (Tümüklü et al 2008) and endurance trained individuals (Vinereanu et al 2002;Zoncu et al 2002;Nottin et al 2004;Kasikcioglu et al 2005;Palka et al 1999;Poulsen et al 2007;Koç et al 2007) have reported elevated tissue Doppler measures of E 0 , E 0 /A 0 or Vp.…”
Section: Impact Of Exercise Training On Diastolic Function: Cross-secmentioning
confidence: 79%
See 2 more Smart Citations
“…In similar subjects, almost identical data (E/A athletes 1.9 ± 0.5 vs. control 1.6 ± 0.2) were either significant (Pluim et al 1998) or non-significant (Pluim et al 1999) based on sample size (21 vs. 12 male cyclists). Cross-sectional or flow propagation data from TDI studies tend to mirror the Doppler flow data described above, with limited differences in E 0 (Caso et al 2000;Schmidt-Trucksäss et al 2001;Pelà et al 2004;Baldi et al 2003), A 0 being similar or lower (Caso et al 2000;Schmidt-Trucksäss et al 2001;Pelà et al 2004;Tümüklü et al 2008;Kasikcioglu et al 2005;Zoncu et al 2002) and generally small improvement in the E 0 /A 0 ratio in athletes compared to untrained subjects. Nonetheless, studies of Olympic speed skaters (Poh et al 2008), professional soccer players (Tümüklü et al 2008) and endurance trained individuals (Vinereanu et al 2002;Zoncu et al 2002;Nottin et al 2004;Kasikcioglu et al 2005;Palka et al 1999;Poulsen et al 2007;Koç et al 2007) have reported elevated tissue Doppler measures of E 0 , E 0 /A 0 or Vp.…”
Section: Impact Of Exercise Training On Diastolic Function: Cross-secmentioning
confidence: 79%
“…Of the studies to specifically report peak E filling velocities, most concluded that there were no differences between athletes and controls (Douglas et al 1986;Caso et al 2000;Sharma et al 2002;Triposkiadis et al 2002;Baldi et al 2003), although a few studies have reported increased E wave velocities in athletes (Karjalainen et al 1997). Conversely, peak A filling velocity is decreased in athletes compared to matched controls (Karjalainen et al 1997;Caso et al 2000;Schmidt-Trucksäss et al 2001;Guazzi et al 2001;Sharma et al 2002;Triposkiadis et al 2002), with only two suggesting no differences (Fagard et al 1987;Baldi et al 2003).…”
Section: Impact Of Exercise Training On Diastolic Function: Cross-secmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal oxygen uptake (V O 2 max ) was measured using the Schiller CS 200 metabolic analyser. A test was accepted as a 'true maximum' according to published criteria [17]. Subject who failed to meet these criteria, or had any other pathological findings during exercise stress testing were not included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…It was recently suggested [3] that following training, the mechanism most likely to be involved is a change in the cardiac autonomic balance producing an increase or a relative dominance of the vegal component. It has long been known that exercise training reduces resting and submaximal heart rate.…”
Section: Exercise Benefitsmentioning
confidence: 99%